Medical student web-based formative assessment tool for renal pathology - Vanesa Bijol; Cathryn J. Byrne-Dugan; Melanie P. Hoenig (Medical Education Online, 2015)
Background: Web-based formative assessment tools have become widely recognized in medical education as valuable resources for self-directed learning. Objectives: To explore the educational value of formative assessment using online quizzes for kidney pathology learning in our renal pathophysiology course. Methods: Students were given unrestricted and optional access to quizzes. Performance on quizzed and non-quizzed materials of those who used (‘quizzers’) and did not use the tool (‘non-quizzers’) was compared. Frequency of tool usage was analyzed and satisfaction surveys were utilized at the end of the course. Results: In total, 82.6% of the students used quizzes. The greatest usage was observed on the day before the final exam. Students repeated interactive and more challenging quizzes more often. Average means between final exam scores for quizzed and unrelated materials were almost equal for ‘quizzers’ and ‘non-quizzers’, but ‘quizzers’ performed statistically better than ‘non-quizzers’ on both, quizzed (p=0.001) and non-quizzed (p=0.024) topics. In total, 89% of surveyed students thought quizzes improved their learning experience in this course. Conclusions: Our new computer-assisted learning tool is popular, and although its use can predict the final exam outcome, it does not provide strong evidence for direct improvement in academic performance. Students who chose to use quizzes did well on all aspects of the final exam and most commonly used quizzes to practice for final exam. Our efforts to revitalize the course material and promote learning by adding interactive online formative assessments improved students’ learning experience overall.